Le risque cyclonique dans l’Atlantique en 2008 - Sandra Rome (EchoGéo)
Hurricane Gustav which approaches the Western coast of Louisiana at the end of August 2008 is presented like one of most intense since Katrina, which earlier has considerably affected the city of News Orleans three years ago. However, if the hazard is comparable, the vulnerability is less in particular because of an effective prevention. This article compares various hurricanes of the Atlantic Ocean, Katrina, Gustav, Hanna and Ike, by differentiating the natural hazard from the vulnerability, especially in Haiti and the United States.